Fatigue design of welded joints using the finite element method and the 2007 ASME Div. 2 Master curve - T. Marin; G. Nicoletto (Fracture and Structural Integrity)
Fatigue design of welded structures is primarily based on a nominal stress; hot spot stress methods or local approaches each having several limitations when coupled with finite element modeling. An alternative recent structural stress definition is discussed and implemented in a post-processor. It provides an effective means for the direct coupling of finite element results to the fatigue assessment of welded joints in complex structures. The applications presented in this work confirm the main features of the method: mesh-insensitivity, accurate crack location and life to failure predictions.